A homogeneous earthquake catalogue for Turkey - Tan, Onur (Natural hazards and earth system sciences, 2021)
A new homogenized earthquake catalogue for Turkey is compiled for the period 1900–2018. The earthquake parameters are obtained from the Bulletin of International Seismological Centre that was fully updated in 2020. New conversion equations between moment magnitude and the other scales (md, ML, mb, Ms, and M) are determined using the general orthogonal regression method to build up a homogeneous catalogue, which is the essential database for seismic hazard studies. The 95 % confidence intervals are estimated using the bootstrap method with 1000 samples. The equivalent moment magnitudes (Mw*) for the entire catalogue are calculated using the magnitude relations to homogenize the catalogue. The magnitude of completeness is 2.7 Mw*. The final catalogue is not declustered or truncated using a threshold magnitude in order to be a widely usable catalogue. It contains not only Mw* but also the average and median of the observed magnitudes for each event. Contrary to the limited earthquake parameters in the previous catalogues for Turkey, the 45 parameters of ∼378 000 events are presented in this study.